Policy gaps and food systems optimization: a review of agriculture, environment, and health policies in South Africa - Hlahla, S.; Ngidi, M.; Duma, S. E.; Sobratee-Fajurally, N.; Modi, Albert Thembinkosi; Slotow, R.; Mabhaudhi, Tafadzwanashe (Frontiers Media, 2023)
South Africa faces the triple burden of malnutrition, high poverty levels, unemployment, and inequality. “Wicked problems” such as these require innovative and transdisciplinary responses, multi-stakeholder coordination and collaboration, managing complex synergies and trade-os, and achieving sustainable outcomes. Through qualitative content analysis of national and provincial sector-based policies, we explored the interlinkages between the agriculture, environment, and health sectors in South Africa in the context of sustainable food and nutrition security and the extent to which these interlinkages are integrated into policy and planning. A systemic analysis of the review outcomes was performed to identify its main learning outcome, the status quo in the policy process. The nature of feedback loops was identified, and a leverage point was suggested. The review highlighted that policymakers in the agriculture, environment and health sectors are aware of, and have understood, the relationships among the three sectors. They have also made attempts to address these interlinkages through collaboration and coordination. Unfortunately, this has been met with several challenges due to fragmented sector-specific mandates and targets and a lack of resources for integrated solutions. This creates implementation gaps and unintended duplication of activities, leading to poor service delivery. Transitioning to sustainable and healthy food systems will only be possible after these gaps have been closed and implementation optimization has been achieved. Focusing on meta-level problem-framing, functional collaboration through transdisciplinary approaches, and integrated targets are critical to successful policy implementation and progressive realization of national goals related to sustainable food and nutrition security, unemployment, poverty, and inequality.